Modeling bioretention stormwater systems: Current models and future research needs. (October 2021) - Lisenbee, Whitney A.; Hathaway, Jon M.; Burns, Matthew J.; Fletcher, Tim D.
Abstract: Many bioretention models still incorporate simplifications and lumped parameters that do not fully account for fundamental physical processes. This review summarizes the representation of hydrologic pathways, notable features, and applications of bioretention models with the goals of recommending models well suited to bioretention modeling and identifying key research needs. As a result, HYDRUS and GIFMod were identified as the only models that use Richards' equation for determining infiltration under variably saturated conditions. Secondly, this study identified limited drainage configurations by most models except DRAINMOD-Urban. Thirdly, most models were inadequate for considering vegetation and plant water use, an area for improvement in future research. Finally, more calibration and validation studies are needed to build confidence in model results. This review intends to educate modelers of the processing equations for each water balance component, the input requirements in each model, and other model characteristics that should be considered in model selection. Graphical abstract: Image 1 Highlights: 17 bioretention models were evaluated for hydrologic and bioretention features. Hydrologic processes were assessed for six models well-suited to bioretention modeling. Major needs in the field of bioretention modeling were identified. Recommendations were given for model selection based on bioretention application.